[LB.01.24] HOME BLOOD PRESSURE NORMALCY IN NON-EUROPEAN ADOLESCENTS. (September 2017) - Jardim, T.; Carneiro, C.; Morais, P.; Mendonça, K.; Povoa, T.; Roriz, W.; Nascente, F.; Barroso, W.; Sousa, A.; Jardim, P.
Abstract : Objective: Evidence on normal range of home blood pressure (BP) in adolescents relies on only one European study. This study aims to investigate the normal range of home BP in a healthy non-European population of adolescents. Design and method: Cross-sectional study with a representative sample of secondary school students (12–17 years) from a Brazilian capital. Adolescents' heights were classified in percentiles according to age and gender. Height percentiles were divided in <=50th or >50th percentile. The home BP protocol included two day-time and two evening-time measurements over 6 days. Exams were considered valid with at least 12 measurements. Results: A total of 1024 adolescents were included, mean age 14.68 ± 1.61 years, predominantly female (52.4%), from public schools (68.4%) and non-white (51.3%). The 50th (midpoint of distribution) and the 95th percentile (upper normal limit) for systolic and diastolic home BP in adolescents are provided by gender, age and height percentiles. There was a marked increase in the estimated 95th percentile for systolic home BP with increasing age in males for both height percentiles examined (16 mmHg for <=50th percentile and 14.5mmHg for >50th percentile) and less so for diastolic home BP (1 mmHg and 5 mmHg, respectively). In females the 95th percentile increase with age was less significant for systolic and similar for diastolic BP when compared to males in the two height percentiles evaluated (6/2 mmHg for <=50th percentile and 4/4 mmHg for >50th percentile). Conclusions: Reference values for home BP by height percentiles for age and sex in a non-European population of adolescents are provided.